Intention to Stay Indonesian Volunteers: The Effect of Autonomy, Competence, Relatedness, Satisfaction and Spirituality - Famdale, Christabel Cheryl; Widyarini, Lydia Ari; Louis, Aloysius Widyawan (PT FORMOSA CENDEKIA GLOBAL, 2025)
The trend of volunteering increases from year to year in the world, but the challanges of retaining volunteers increased because it depends solely on their intent to stay. Therefore, volunteer satisfaction needs to be achieved. Self Determination Theory (SDT) offers three dimensions, namely autonomy, competence, and connectedness to elaborate individual's intrinsic motivation to feel satisfied. When these three needs are met, theoretically a person will feel satisfied at work. This research aims to examine and analyze the influence of fulfilling their psychological needs on job satisfaction thus satisfied volunteers are more willing to stay longer and see how work spirituality influences this relationship. The research results show that there is a significant influence between job satisfaction and intention to stay.